Neurofilaments and progranulin are related to atrophy in frontotemporal lobar degeneration – A transdiagnostic study cross-validating atrophy and fluid biomarkers - Hüper, Lea; Steinacker, Petra; Polyakova, Maryna; Mueller, Karsten; Godulla, Jannis; Herzig, Sabine; Danek, Adrian; Engel, Annerose; Diehl-Schmid, Janine; Classen, Joseph; Fassbender, Klaus; Fliessbach, Klaus; et al. (Alzheimers & Dementia, 2024)
INTRODUCTION: Frontotemporal lobar degeneration (FTLD) encompasses behavioral variant frontotemporal dementia (bvFTD), progressive supranuclear palsy, corticobasal syndrome/degeneration, and primary progressive aphasias (PPAs). We cross-validated fluid biomarkers and neuroimaging. METHODS: Seven fluid biomarkers from cerebrospinal fluid and serum were related to atrophy in 428 participants including these FTLD subtypes, logopenic variant PPA (lvPPA), Alzheimer's disease (AD), and healthy subjects. Atrophy was assessed by structural magnetic resonance imaging and atlas-based volumetry. RESULTS: FTLD subtypes, lvPPA, and AD showed specific profiles for neurofilament light chain, phosphorylated heavy chain, tau, phospho-tau, amyloid beta1-42 from serum/cerebrospinal fluid, and brain atrophy. Neurofilaments related to regional atrophy in bvFTD, whereas progranulin was associated with atrophy in semantic variant PPA. Ubiquitin showed no effects. DISCUSSION: Results specify biomarker and atrophy patterns in FTLD and AD supporting differential diagnosis. They identify neurofilaments and progranulin in interaction with structural imaging as promising candidates for monitoring disease progression and therapy. Highlights: Study cross-validated neuroimaging and fluid biomarkers in dementia. Five kinds of frontotemporal lobar degeneration and two variants of Alzheimer's disease. Study identifies disease-specific fluid biomarker and atrophy profiles. Fluid biomarkers and atrophy interact in a disease-specific way. Neurofilaments and progranulin are proposed as biomarkers for diagnosis and therapy.
CRIS-Team Scopus Importer:2024-06-21
Keywords: amyloid; atrophy; fluid biomarkers; frontotemporal dementia; frontotemporal lobar degeneration; magnetic resonance imaging; neurofilaments; phospho-tau; progranulin; tau; ubiquitin